Societal stigma and mistreatment in healthcare among gender minority people: a cross-sectional study - Kristen D. Clark; Mitchell R. Lunn; Jordon D. Bosse; Jae M. Sevelius; Carol Dawson-Rose; Sandra J. Weiss; Micah E. Lubensky; Juno Obedin-Maliver; Annesa Flentje (International Journal for Equity in Health, 2023)
Abstract Background Gender minority (GM; individuals whose gender is not aligned with that traditionally associated with the sex that was assigned to them at birth) people have widely reported mistreatment in healthcare settings. Mistreatment is enacted by individuals within society who hold stigmatizing beliefs. However, the relationship between healthcare mistreatment and societal stigma (i.e., the degree to which society disapproves of GM people) is unclear and not measured consistently. Methods We analyzed data from 2,031 GM participants in The Population Research in Identity and Disparities for Equality (PRIDE) Study’s 2019 Annual Questionnaire to determine whether societal stigma was associated with participants’ past-year reports of mistreatment (defined as denial of healthcare services and/or lower quality care) in medical or mental healthcare settings. We created a proxy measure of societal stigma by incorporating variables validated in existing literature. Participants reported whether they had experienced mistreatment in medical and mental health settings independently. Results Healthcare denial and/or lower quality care during the past year was reported by 18.8% of our sample for medical settings and 12.5% for mental health settings. We found no associations between the societal stigma variables and past-year reports of healthcare denial and/or lower quality care in medical or mental healthcare settings. Conclusions Although a high proportion of GM people reported past-year healthcare mistreatment in both medical and mental health settings, mistreatment had no relationship with societal stigma. Factors other than societal stigma may be more important predictors of healthcare mistreatment, such as healthcare workers’ knowledge of and attitudes toward GM people. However, other measures of societal stigma, or different types of mistreatment, may show stronger associations. Identifying key factors that contribute to mistreatment can serve as targets for intervention in communities and healthcare settings.